Integrating Project-Based Learning and Community Outreach for Science Communication “A Case Study in the Chemistry Project Course.”: - Ratika Ssaputri; Ervina (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
21th century chemistry education requires students to master scientific concepts while developing science communication skills relevant to societal needs. However, the gap between theoretical classroom learning and its real-world application remains a significant educational challenge. This study aims to explore the implementation of the Project-Based Learning–Exhibition-Based Community Outreach (PjBL-ECO) model to enhance students’ content mastery and science communication skills. This research employed a qualitative approach with a case study design involving Tadris Kimia students enrolled in the Chemistry Project course. Data were collected through participant observation, in-depth interviews, documentation, and students’ written reflections. The data were analyzed using thematic analysis to identify patterns of meaning emerging from participants’ experiences. The findings revealed three major themes: the transformation of conceptual understanding through authentic experiences, the negotiation of meaning in science communication, and the development of professional identity and social awareness. These findings reflect a dialogic, reflective, and contextual learning process within academic and community settings. The study confirms that the PjBL-ECO model strengthens constructivist learning and science communication while supporting innovative curriculum development and enhancing public scientific literacy.